Kreativitas Sekolah dalam Mewujudkan Sekolah Efektif di Kabupaten Aceh Besar (Studi Kasus pada SD Negeri I Lam Cot) - Nurmalawati, Nurmalawati; Akmaluddin, Akmaluddin; Mukhlisuddin, Mukhlisuddin (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to find out the process of creativity of school principals, obstacles faced by school principals and what solutions are taken by school principals to improve teacher effectiveness in learning at SD Negeri 1 Lamcot Aceh Besar Regency. This research is qualitative with a descriptive approach, namely observation, interviews, and documentation. The data analysis process is carried out qualitatively with the stages of data reduction, data presentation, and conclusions. The results of the research show that the managerial creativity process of school principals improves the quality of learning by increasing teacher abilities through coaching in the learning process. The second step is to increase teacher discipline or enforce teacher discipline, increase teacher behavior standards, and implement all regulations. The third step, increasing teacher motivation, is to create a harmonious situation, fulfill all the necessary equipment and provide rewards and punishments. The fourth step, I hold training, bring tutors to schools, and provide opportunities to continue their education, assign teachers according to their fields, and hold meetings at the beginning of each semester